THE RELATIONSHIP BETWEEN LANGUAGE AND CULTURE IN EFL LEARNING - Abdukarimova Qadriya (International Journal of Literature and Language Studies, 2026)
The relationship between language and culture is one of the most significant aspects of English as a Foreign Language (EFL) learning. Language is not merely a means of communication; it is also a carrier of cultural values, beliefs, traditions, and social experiences. Therefore, understanding cultural aspects is essential for developing effective communicative competence in language learners. This article examines the interconnection between language and culture, the role of culture in EFL education, intercultural communicative competence, and modern approaches to integrating culture into language teaching. The study highlights the importance of cultural awareness in achieving successful language learning outcomes.